. PENGEMBANGAN KECERADASAN INTERPERSONAL PESERTA DIDIK MTS KHATIBUL UMAM KURMA: PENGEMBANGAN KECERADASAN INTERPERSONAL PESERTA DIDIK MTS KHATIBUL UMAM KURMA - Taupik. C Taupik. C; Rezky Mutmainnah (IAI DDI POLEWALI MANDAR, 2023)
The problem studied in this research is how to develop the interpersonal intelligence of MTs Khatibul Umam Kurma students and what factors influence the development of interpersonal intelligence of MTs Khatibul Umam Kurma students. The type of research used is descriptive qualitative research. The data collection method is carried out by observation or observations and interviews based on facts in the field. The research results explained that the development of interpersonal intelligence of MTs Khatibul Umam Kurma students is active learning and learning with a social aspect approach. Another way for teachers is through group assignments, peer tutoring, questions and answers and demonstrations. Next are the steps taken, namely preparation, organizer and evaluation. The influencing factors are supporting and inhibiting factors. Supporting factors include: (1) Educators are experts and professionals. (2) Adequate facilities and infrastructure. The inhibiting factors are (1) Different family backgrounds and environments, (2) The potential and attitudes of each child are different.